Effect of integrated nutrient management practices on productivity of durumm wheat (Triticum durum) in the Vertisols of central India - BEHERA, U K; PRADHAN, S; SHARMA, A R (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2000-01 and 2001-02 on fine-textured Vertisols at Indore to study the effect of combined use of farmyard manure and poultry manure with 50 and 100% NPK on productivity, grain quality and proftability of durunz wheat (Triticum durunz Desf.). The grain yield of durum wheat was significantly increased with integrated use of 50% or 100% NPK + poultry manure @ 2.5 tonneska or farmyard manure @ 10 tonnes/ha compared with inorganic fertilizers alone. The yield improvement was 13.5 and 22.9% and 11.4 and 14.5 % with farmyard manure and poultry manure at 50 and 100% recommended NPK respectively over the sole application of inorganic. The highest productivity was obtained when these organic sources were applied along with 100% NPK, indicating that NPK fertilizers alone did not provide adequate and balanced nutrition to realize the potential yield of the crop. Quality parameters of durum grains, viz protein content and hectolitre weight increased, while yellow berry content decreased with increasing levels of NPK compared with control. Sole application of inorganic fertilizers was equally efficient with their combined use with organics in improving the quality parameters.